Service multinational enterprises and linkages development in Pakistan - Khan, Zaheer; Park, Jeong-Yang; Pervaiz, Akhtar (Wiley, 2017)
The development of various types of linkages is key for understanding the impact of multinational enterprises (MNEs) on the economic development of host markets. By utilizing qualitative research approach, this paper investigates the linkages creation by IT MNEs in Pakistan. The findings suggest that these MNEs have created various linkages such as management, technological, diversification and financial linkages. The creation of these linkages was contingent and co-determined by the MNEs' investment motives, their mandates and embeddedness in the host market as well as the local technical capability. The paper highlights the contributions and the implications of these linkages.